Perbandingan Perbandingan Pengaruh Problem Based Learning Dan Inquiry Based Learning Terhadap Kemampuan Literasi Numerasi Siswa - Irma Safira; Heni Pujiastuti; Fakhrudin Fakhrudin (Griya Journal of Mathematics Education and Application, 2026)
This study compares the effect of Problem Based Learning (PBL) and Inquiry Based Learning (IBL) learning models on students' numeracy literacy skills. The objectives of the study were to describe students' numeracy literacy skills using both models, to determine the differences in their effects, and to test the improvement in students' abilities after implementation. The study used a quasi-experimental design involving 60 eighth-grade students of SMP Negeri 1 Padarincang who were divided into two experimental groups. Data were collected through pretests and posttests of numeracy literacy. The results showed that students who learned using the IBL model had higher numeracy literacy skills and more significant improvements compared to the PBL model. It was concluded that the IBL model was more effective in improving students' numeracy literacy.